Estrogen and progesterone receptors - Bellido B., Percy (2015)
Estrogen therapy is increasing and this requires an adequate knowledge of the mechanism of action of steroids, being known when transport and metabolism. Therefore we discuss the molecular aspects of estrogen action at the level of nuclear receptors, specifying the structure and operation thereof. Transcription factors is reviewed, describing their DNA binding domains and activation. Transcription accuracies, the paper polymerase II and general transcription factors, forming the transcription initiation complex. Culminates exposing how the regulation of receptor concentration through the mechanism of filling and pointing out some clinical implications. Estrogen therapy is increasing and is appropriate for use is the result of a proper understanding of the mechanism of action of estrogen in the target cell; This knowledge allows us to understand biomolecular individual or group response to such therapy. The hormone estrogen and progesterone receptors have been found and studied throughout the organismo1-3 and are part of the regulation of internal med¡o; It explains understanding steroid hormone physiology.